P325 Proton pump inhibitors are associated with a disabling course of Crohn's disease. (30th January 2023) - Barrau, M; Duru, G; Nancey, S; Phelip, J M; Cheifetz, A; Papamichael, K; Paul, S; Xavier, R
Abstract: Background: The impact of proton pump inhibitors (PPIs) on the evolution of inflammatory bowel disease (IBD) remains debated with only sparse data available. The primary objective of this study was to analyze the impact of PPIs on the course of IBD. Methods: This was a single-center, retrospective cohort study. We included consecutive adult patients diagnosed with Crohn disease (CD) or ulcerative colitis (UC) who were followed prospectively in our day hospital over a 4-month period (from May to August 2022). PPI exposure was defined as PPI use for a cumulative duration of more than seven days from the date of IBD diagnosis until the end of follow-up. We performed a time to event analysis to investigate the association of PPI exposure with treatment failure defined as an IBD-related surgery or hospitalization and/or failure for more than four biologic treatment (Anti TNF, Vedolizumab, Ustekinumab). Results: Among the 281 patients identified, 244 patients were eligible for analysis of the primary objective (152 with CD, mean age 45 years, sex ratio 1:1). 113 (46%) patients had been previously exposed to a PPI. PPI-exposed patients were significantly older (p=0.013), more often women (p=0.029), with more frequent active smoking (p=0.001). A total of 152 patients (62%) had treatment failure. Using Cox regression analysis, (Table 1), PPI use identified as an independent factor associated with treatment failure (HR = 1.920; 95% CI [1.084-3.403]; p0.025). In a subgroup analysis by IBD type, this remained statistically significant only for CD (HR = 3.190; 95% CI (1.412-7.206); p 0.005) but not for UC (HR = 0.981; 95% CI (0.384-2.504); p0.968). Survival without treatment failure (Figure 1) was significantly higher in patients without PPI exposure compared to patients with PPI exposure, (325 months vs. 228 months, respectively, p=0.022 (Log-Rank). In a subgroup analysis of infliximab-treated patients, PPI use was not associated with risk of immunogenicity (HR = 1.071; 95% CI (0.515-2.226); p0.854). Conclusion: This study demonstrates the negative impact of PPIs on the disease course in patients with CD. The use PPIs should better be discussed on a case-by-case basis.